The Revised Ordinances of the City of Portland, 1848 Page 22, Image 22 (1848) §§ 1-4 - (:unkn) unknown (General Publisher, 1848)
No person not licensed to keep and sell gunpowder shall keep or have in his shop, store, dwelling house or other tenement, at any one time, a larger quantity of gunpowder than one pound. § 2. No person licensed to keep and sell gunpowder shall have or keep in his store, shop, dwelling house or in any other tenement or place whatever at any one time, a larger quantity of gunpowder then twenty-five pounds.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER